Laplace’s Demon: The Deterministic versus the Probabilistic Nature of the Universe - Izmirli, Ilhan M. (Transactions on Engineering and Computing Sciences, 2026)
Essai philosophique sur les probabilités (A Philosophical Essay on Probability) was a nontechnical exposition of the laws of chance written by Pierre-Simon Laplace in 1814 as an elaboration of a lecture delivered at the École Normale in 1795. In contrast to his monumental 1812 treatise, Théorie analytique des probabilités (The Analytical Theory of Probability), Laplace sought to introduce the concept of probability independently of the methods of calculus and to demonstrate that probabilistic reasoning permeates all aspects of human existence, including expectation, uncertainty, hope, and fear. He concluded the introduction of the essay with the observation: I hope that the reflections given in this essay may merit the attention of philosophers and direct it to a subject so worthy of their engaging minds. This philosophical program, however, gave rise to a profound conceptual tension. Specifically, Laplace was compelled to reconcile the apparent randomness inherent in probabilistic phenomena with his uncompromising commitment to universal determinism. This tension culminated in the celebrated thought experiment commonly referred to as Laplace’s Demon: the hypothetical intelligence capable of knowing, at a given instant, all forces acting in nature together with the precise positions and motions of every particle in the universe. Under such conditions, Laplace argued, the future and the past would be entirely determined and therefore fully predictable. The coexistence of probabilistic analysis and strict determinism remains one of the most significant philosophical issues in the foundations of probability theory and the philosophy of science.